Estimation of Arterial Mechanical Properties from Aortic and Tonometric Arterial Pressure Waveforms - Sugimachi, M.; Kawada, T.; Shishido, T.; Matsumoto, N.; Alexander, J.; Sunagawa, K. (Methods of Information in Medicine, 1997)
Although arterial mechanical properties have been evaluated using arterial input impedance, the relative difficulty in accurate flow measurement made the value of impedance somewhat limited. To develop an alternative method to evaluate arterial mechanical properties, we analyzed the aortic pressure (AoP)-radial arterial pressure (RAP) relationship because of relative ease in obtaining peripheral pressure waveform by tonometry. In 8 patients we simultaneously recorded aortic root and radial arterial pressure waveforms. We calculated the transfer function from AoP to RAP. We then fitted the transfer function to a model of a lossless uniform elastic tube terminated with a modified Windkessel model. The fact that the model transfer function predicted AoP from RAP waveform with considerable accuracy indicated that the model represented the arterial mechanical properties well. We conclude that we can estimate the arterial mechanical properties by the pressure-pressure transfer function analysis.
Keywords: Transfer Function; Random Noise Technique; Arterial Reflection